2010
DOI: 10.1179/146701010x12726366068292
|View full text |Cite
|
Sign up to set email alerts
|

Speech Discrimination Scores Using the Latest Generation of Speech Processors

Abstract: The Manchester Cochlear Implant Programme was established in 1988 and over 1000 patients have been implanted to date. Developments and improvements in cochlear implant technology over the past 21 years have resulted in new generations of implants and speech processors becoming available for use with patients. Since 2004, our patients have been asked to choose a device, based on their own preferences.This study looks at the speech discrimination scores of adults fitted with the latest generation of speech proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…The manufacturers are similar in terms of customer support and are continually developing more sophisticated speech-processing strategies and algorithms. The latest generation processors offer better speech discrimination scores than the old generation of processors in adults and the biggest improvement was seen between 1 week and 3 months (Brough et al, 2010) irrespective of the device. In the current service evaluation, the most common reason reported by the patients and the parents of the children was related to comfort and fit, looks, and size of the processor.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The manufacturers are similar in terms of customer support and are continually developing more sophisticated speech-processing strategies and algorithms. The latest generation processors offer better speech discrimination scores than the old generation of processors in adults and the biggest improvement was seen between 1 week and 3 months (Brough et al, 2010) irrespective of the device. In the current service evaluation, the most common reason reported by the patients and the parents of the children was related to comfort and fit, looks, and size of the processor.…”
Section: Discussionmentioning
confidence: 91%
“…It is surprising that not many patients and parents of the children spoke about the technology aspect of the implants as their reason for choosing a particular device. Brough et al (2010) reported that even after informing the patients about the different trends in the outcomes with different devices to help the patients to make an informed choice, the information does not seem to influence the choice of device. Some of the patients find choosing a device a difficult task: in such scenarios the clinicians would suggest that the patient takes time to feel the controls on the processors to determine which might be the easiest to use, particularly if they experience problems with dexterity and/or vision.…”
Section: Discussionmentioning
confidence: 99%